1997
DOI: 10.1063/1.166248
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of self-propagating polymerization fronts: The role of kinetics on front stability

Abstract: Frontal propagation of a highly exothermic polymerization reaction in a liquid is studied with the goal of developing a mathematical model of the process. As a model case we consider monomers such as methacrylic acid and n-butyl acrylate with peroxide initiators, although the model is not limited to these reactants and can be applied to any system with the similar basic polymerization mechanism. A three-step reaction mechanism, including initiation, propagation and termination steps, as well as a more simple o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 19 publications
1
54
0
Order By: Relevance
“…Solovyov et al performed two-dimensional numerical simulations using a standard three-step free-radical mechanism [92]. They calculated the Zeldovich number from the overall activation energy using the steady-state theory and determined the critical values for bifurcations to periodic modes and found that the complex kinetics stabilized the front.…”
Section: Effect Of Complex Kineticsmentioning
confidence: 99%
“…Solovyov et al performed two-dimensional numerical simulations using a standard three-step free-radical mechanism [92]. They calculated the Zeldovich number from the overall activation energy using the steady-state theory and determined the critical values for bifurcations to periodic modes and found that the complex kinetics stabilized the front.…”
Section: Effect Of Complex Kineticsmentioning
confidence: 99%
“…The numerically determined behavior of the front for the step-function kinetics is qualitatively similar to that under the Arrhenius kinetics [7], [18], as it shows a similar hierarchy of dynamics and similar solution features, including those that result from the nonfrontal mode of polymerization. The same spectrum of system behaviors has also been demonstrated for the point-source kinetics [9]; however, all bulk (nonfrontal) reactions are ignored in this setting.…”
Section: Physical Background and Existing Modeling Approachesmentioning
confidence: 61%
“…Such nonplanar modes of propagation have been the subject of much investigation. 40,[45][46][47][48][49][50][51] The complexity of the front increases with the value of the effective energy of activation. By reducing the number of propagating radicals, the transition metal reduces the contribution of the energy of activation for the termination step, which increases the effective activation energy.…”
Section: Resultsmentioning
confidence: 99%